PERBANDINGAN FOREIGN DIRECT INVESTMENT NEGARA MYANMAR DENGAN INDONESIA - Artharini, Nadia Feby (Faculty of Law, Tanjungpura University, 2021)
AbstractÂ This journal discusses about comparative law on Myanmar's Foreign Direct Investment with Indonesianâ€™s FDI. The study uses a literature study of secondary data. The results of the study are the identification of regulations concerning Myanmar's Foreign Direct Investment compared to Foreign Direct Investment in Indonesia. Related to Foreign Direct Investment, there are several main aspects in the applicable regulations, which must be fulfilled such as the agency that deals with, special investment policies, business fields that are established and restricted to foreigners, the obligations of investors, partner institutions relevant to Myanmar's FDI, investment aggregation as well as the type of investment and guarantee provided to investors in Myanmar.AbstrakÂ Jurnal ini membahas mengenai perbandingan hukum Foreign Direct Investment Negara Myanmar dengan Indonesia. Penelitian menggunakan studi kepustakaan terhadap data sekunder. Hasil penelitian adalah identifikasi peraturan-peraturan yang memuat perihal Foreign Direct Investment negara Myanmar dibandingkan dengan Foreign Direct Investment di Indonesia. Terkait Foreign Direct Investment, terdapat beberapa aspek utama dalam peraturan-peraturan yang berlaku, yang harus dipenuhi seperti lembaga yang mengurusi, kebijakan investasi khusus, bidang usaha yang terbuka dan yang dibatasi untuk asing, kewajiban para investor, institusi mitra yang relevan dengan FDI Myanmar, investment aggrement serta jenis investasi dan garansi yang diberikan kepada para inveestor di Myanmar.